Problem of fuel losses owing to evaporation during operation of air engineering - Бойченко C. B. (Proceedings of National Aviation University (archive), 1999)
Considered is the problem of irrevocable losses of air fuel which happen owing to evaporation in conditions of operation of air engineering, particularly in flight time of airplane. Composed is generalized performance of fuel losses from evaporation in conditions of flight of airplane